Analysis of Product Differentiation on Customer Satisfaction and The Effect on Customer Loyalty at Jomtea Batam - Raudhatul Fauziah; Shinta Wahyu Hati (Jurnal Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the effect of product differentiation and its implications on customer satisfaction on customer loyalty either partially or simultaneously. The population are people who have bought Jomtea product with 100 respondents as sample using purposive sampling technique. The analysis technique applied for hypothesis testing is path analysis. The results show that product differentiation had a positive and significant effect on customer loyalty. With an R Square value of 0.788, this shows that the variables of price, uniqueness, and brand image are 78.8% simultaneously able to influence customer loyalty through Jomtea customer satisfaction in Batam City, while 0.212 or 21.2% are obtained from other variables. Based on path analysis, it was found that the customer satisfaction variable as an intervening variable was declared unablelto mediate the relationship between exogenous variables and endogenous variables.